2014
DOI: 10.1371/journal.pone.0111025
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium Trans Differentiated from Wharton's Jelly Mesenchymal Cells Promote Tissue Regeneration: Potential Role of Soluble Pro-Angiogenic Factors

Abstract: BackgroundMesenchymal stem cells have a high capacity for trans-differentiation toward many adult cell types, including endothelial cells. Feto-placental tissue, such as Wharton's jelly is a potential source of mesenchymal stem cells with low immunogenic capacity; make them an excellent source of progenitor cells with a potential use for tissue repair. We evaluated whether administration of endothelial cells derived from mesenchymal stem cells isolated from Wharton's jelly (hWMSCs) can accelerate tissue repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 56 publications
(99 reference statements)
0
31
0
1
Order By: Relevance
“…Tie-2 expression was raised to various degrees in BMSCs, AMSCs, and PMSCs during endothelial differentiation, but with a falloff in UMSCs. To better define the expression of endothelial-related proteins and the unique functions of cells after endothelial differentiation, an immunostaining assay [20, 21] and an acLDL-uptaking assay [22] were performed respectively (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tie-2 expression was raised to various degrees in BMSCs, AMSCs, and PMSCs during endothelial differentiation, but with a falloff in UMSCs. To better define the expression of endothelial-related proteins and the unique functions of cells after endothelial differentiation, an immunostaining assay [20, 21] and an acLDL-uptaking assay [22] were performed respectively (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Aguilera et al . [20] demonstrated that Wharton’s jelly-derived mesenchymal cells expressed high levels of endothelial markers (CD31 and KDR) and also synthesized NO after 30 days of endothelial differentiation. Additionally, Ikhapoh et al [35] and Benavides et al [21] respectively reported that BMSC and amniotic fluid-derived stem cells were capable of differentiation into endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, WJMSC may represent a much better choice, as they are much easily attainable, exhibit excellent proliferative and differentiation potential, pose no ethical concern, and are of invariant, consistent, young age. However, only recently has interest emerged towards WJMSCs and their promising therapeutic potential (Aguilera et al, 2014;Batsali et al, 2013;Hsieh et al, 2013).…”
Section: Potential Of Msc In the Treatment Of Peripheral Nerve Injurymentioning
confidence: 99%
“…Confluent MSCs are sensitive to VEGF differentiation mediated by KDR activation. A slight variation of KDR for WJ‐ and BM‐MSCs on both coatings is probably due to the absence of VEGF in EBM‐2 ® . Related to mRNA regulation, the corresponding protein synthesis, by WJ‐ and BM‐MSCs, was evaluated by Western blot.…”
Section: Resultsmentioning
confidence: 99%